Effectiveness of Helichrysum italicum Essential Oil on Wound Healing - Linda Julianti Wijayadi; Kelvin Kelvin (Journal of Food and Pharmaceutical Sciences, 2022)
Helichrysum italicum essential oils (EOs) has long been known as a medicinal agent, especially in wound healing. This is inseparable from the chemical compounds contained in it, such as abundant monoterpenes and sesquiterpenes. The purpose of this systematic review is to examine various studies on the effectiveness of H. italicum EOs on wound healing. Research data searches were conducted through Google Scholar, Proquest, Science Direct, SpringerLink, Wiley Online Library, Taylor & Francis Online and PubMed over the last 10 years by following inclusion and exclusion criteria. Obtained as many as 11 studies that match the criteria. Based on the review of these studies, it was found that H. italicum EOs has good wound healing abilities when viewed from various aspects such as its chemical components, biological activity and its effect on injured body tissues. These chemical components vary in type and amount because they are influenced by various aspects. Biological activities such as antioxidant, antimicrobial, and anti-inflammatory effects have also been shown to be contained in this oil because it affects various phases of wound healing, namely hemostasis, inflammation, proliferation and remodeling phases. This is also inseparable from the accuracy of the type of vehicle used.